Encapsulation of Anthocyanins and the Factors Affecting Their Stability as Natural Colorants in Food Products - Holinesti, Rahmi; Yusniwati; Anggraini, Tuty; Syukri, Daimon (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Colorants are commonly added to food products to enhance their visual appeal and increase consumer interest. Among the various types of natural pigments, anthocyanins—derived from fruits, vegetables, flowers, and tuberous plants—have garnered significant scientific interest due to their vivid coloration and associated health-promoting properties. Nevertheless, anthocyanins exhibit considerable sensitivity to environmental variables, including temperature, pH, oxygen exposure, ultraviolet (UV) radiation, and interactions with other molecular constituents. A range of environmental stressors can accelerate the deterioration of anthocyanin pigments during processing and storage, leading to a decrease in colour intensity. To counteract these destabilizing influences, various encapsulation strategies have been developed to protect anthocyanins from degradation. Among these, spray drying is widely recognized for its efficacy in maintaining both the physicochemical integrity and biofunctional performance of anthocyanin molecules. This review discusses the strategic importance of encapsulation in enhancing anthocyanin stability and examines the primary degradation mechanisms relevant to their application in food systems. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-BeingSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production